2019
DOI: 10.1002/adfm.201908047
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Polymer–Lithium Interface in a Rechargeable Solid Battery

Abstract: Solid polymer electrolytes (SPEs) are promising candidates for developing highenergy-density Li metal batteries due to their flexible processability. However, the low mechanical strength as well as the inferior interfacial regulation of ions between SPEs and Li metal anode limit the suppress ion of Li dendrites and destabilize the Li anode. To meet these challenges, interfacial engineering aiming to homogenize the distribution of Li + /electron accompanied with enhanced mechanical strength by Mg 3 N 2 layer de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 37 publications
1
55
0
Order By: Relevance
“…Therefore, various interfacial engineering methods have been explored, mainly focusing on high electronic conducting, mixed ionic-electronic conducting and ionic conducting but electronic insulating interlayers. Recently, coating metals, such as Si [78] , Mg [20] , Al [23,79] and Ge [19] , or metal oxides, like Al 2 O 3 [19] and ZnO [22] , can trigger an alloying reaction with Li and form high electronic conducting Li-metal alloy interlayers. Li-metal alloy interlayers exhibit excellent lithiophilicity with Li and significantly improve the physical contact, leading to an even current distribution and low interfacial resistance [Figure 4C].…”
Section: Surface Energy and Chemical Interactionsmentioning
confidence: 99%
“…Therefore, various interfacial engineering methods have been explored, mainly focusing on high electronic conducting, mixed ionic-electronic conducting and ionic conducting but electronic insulating interlayers. Recently, coating metals, such as Si [78] , Mg [20] , Al [23,79] and Ge [19] , or metal oxides, like Al 2 O 3 [19] and ZnO [22] , can trigger an alloying reaction with Li and form high electronic conducting Li-metal alloy interlayers. Li-metal alloy interlayers exhibit excellent lithiophilicity with Li and significantly improve the physical contact, leading to an even current distribution and low interfacial resistance [Figure 4C].…”
Section: Surface Energy and Chemical Interactionsmentioning
confidence: 99%
“…Similarly, AFM in PeakForce Tunnelling mode showed that an intermediary Mg 3 N 2 layer between Li metal anode and PEO SSE enabled a smoother, more robust surface with a more homogeneous current distribution on the Li anode surface (Figure 13c–f). [ 288 ] This facilitated homogeneous Li plating/stripping and promoted fast Li ion kinetics.…”
Section: Ec‐afm For the Understanding Of Libs And Their Materialsmentioning
confidence: 99%
“…Reproduced with permission. [ 288 ] Copyright 2020, Wiley‐VCH. AFM images of the surface of g) silver and h) gold interlayers at various charge/discharge states: pristine, after 0.2 mA cm −2 galvanostatic deposition for 15 and 150 min, and 0.1 mA cm −2 galvanostatic stripping of lithium.…”
Section: Ec‐afm For the Understanding Of Libs And Their Materialsmentioning
confidence: 99%
“…[ 35 ] These modification schemes provide new concepts to modify Li metal anodes, and the combination of fast Li + conductor modification layer and alloy modification layer may show advantages to suppress Li dendrites. [ 36–39 ] As previous reported, electronic or Li + conductors were chosen as artificial SEI for lithium anode, such as LiAl, [ 40 ] LiPb, [ 41 ] LiSn, [ 42 ] LiZn, [ 43 ] Li 2 S, [ 44,45 ] Li 3 PS 4 , and [ 46 ] Li 3 N. [ 47–50 ] Recently, a novel artificial SEI modification method has been developed with dual‐conductive artificial layer for lithium anode, such as LiF/AlLi, [ 51 ] LiF/Cu, [ 52,53 ] Li 3 N/LiMg, [ 54 ] Cu/Li 3 N, [ 55 ] and LiCl/LiIn/LiZn/LiBi/LiAs. [ 56 ] For example, Yan [ 57 ] achieved remarkable results in inhibiting lithium dendrite with LiNO 3 as the ionic‐conductive additive.…”
Section: Introductionmentioning
confidence: 99%